Spatiotemporal Pattern of Soil Respiration of Terrestrial Ecosystems in China: The Development of a Geostatistical Model and Its Simulation - Yu, Guirui; Zheng, Zemei; Wang, Qiufeng; Fu, Yuling; Zhuang, Jie; Sun, Xiaomin; Wang, Yuesi (Environmental science & technology, 2010)
Quantification of the spatiotemporal pattern of soil respiration (R s) at the regional scale can provide a theoretical basis and fundamental data for accurate evaluation of the global carbon budget. This study summarizes the R s data measured in China from 1995 to 2004. Based on the data, a new region-scale geostatistical model of soil respiration (GSMSR) was developed by modifying a global scale statistical model. The GSMSR model, which is driven by monthly air temperature, monthly precipitation, and soil organic carbon (SOC) density, can capture 64% of the spatiotemporal variability of soil R s . We evaluated the spatiotemporal pattern of R s in China using the GSMSR model. The estimated results demonstrate that the annual R s in China ranged from 3.77 to 4.00 Pg C yr−1 between 1995 and 2004, with an average value of 3.84 ± 0.07 Pg C yr−1, contributing 3.92%−4.87% to the global soil CO2 emission. Annual R s rate of evergreen broadleaved forest ecosystem was 698 ± 11 g C m−2 yr−1, significantly higher than that of grassland (439 ± 7 g C m−2 yr−1) and cropland (555 ± 12 g C m−2 yr−1). The contributions of grassland, cropland, and forestland ecosystems to the total R s in China were 48.38 ± 0.35%, 22.19 ± 0.18%, and 20.84 ± 0.13%, respectively.